Analysis of the Fundamental Frequency F0 of Oesophageal Speech in Patients Following Total Laryngectomy Surgery - Krzysztof Tyburek (Applied Sciences)
The aim of this article is to analyse the fundamental frequency of oesophageal speech (ES) F0 and compare the results with the physiological speech of healthy people. The research focused on spectrogram analysis, taking into account a frequency range that is appropriate for both people following total laryngectomy and healthy people. Therefore, the frequency range of 50 Hz to 200 Hz was proposed for the research. The studied fundamental frequency F0 was determined by segmenting the speech signal using a moving time window. As a result, a frequency vector F0 (for each tested word) was obtained, the length of which depends on the number of frames. The obtained set of fundamental frequencies (pitch listing) was analysed using statistical functions, which led to the determination of the F0 distribution in the range of minimum, maximum, median, and standard deviation values. Voice samples were taken from 12 people aged between 30 and 70 following total laryngectomy. In accordance with the rehabilitation process, words (spoken in Polish) such as “barrel”, “bread roll”, “egg”, “package”, and “snow” were analysed (each as a separate pattern).